Differentiated teaching materials with an Islamic values approach in the differential calculus course - Novi Andri Nurcahyono; Aritsya Imswatama; Arif Yudianto (Research and Development in Education (RaDEn), 2024)
Students' needs in the learning process are different. For this reason, learning needs to be designed according to student characteristics in order to obtain optimal results. Apart from that, it is also necessary to pay attention to the values that will be given in each learning process. This is because the aim of education is not only human development, apart from science and technology, but also development from the faith and piety side, so that it can optimize the potential that is possessed both cognitively and socio-emotionally. So the aim of this research is to develop teaching materials based on differentiated learning with an Islamic values approach in the Differential Calculus course. This research uses a Research and Development approach. The development model used is the ADDIE model. Limited trials showed that the teaching materials developed obtained a percentage of 85% (very suitable) for use. There is differentiation in processes, material content and learning products and integration of Islamic values in the teaching materials developed.